Overexpression of Setaria italica phosphoenolpyruvate carboxylase gene in rice positively impacts photosynthesis and agronomic traits - Behera, Deeptirekha (Plant physiology and biochemistry : PPB, 2023)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.